Immediate Impact of Centralization on Abdominal Aortic Aneurysm Repair Outcomes for a Vascular Network in the South West of England: A Retrospective Cohort Study. Issue 1 (January 2019) - Leighton, Philippa; Doe, Matthew; Pathak, Samir; AlDuwaisan, Abdullah; Brooks, Marcus
Abstract : Objective: Our aim was to assess the short-term impact of centralization on the outcomes of patients undergoing abdominal aortic aneurysm repair in a vascular network in the South West of England. Background: The centralization of vascular services has been implemented nationally across the National Health Service to improve patient outcomes. The full impact of these major changes has not yet been fully analyzed. Methods: A retrospective cohort study examining outcomes of patients undergoing abdominal aortic aneurysm repair, based on prospectively entered National Vascular Registry data, pre and post centralization in the South West of England. The primary outcome was mortality at 30 days. Secondary measures included 30-day morbidity, length of hospital stay, and length of intensive care unit stay. Results: The 30-day mortality was unchanged pre and post-centralization (11% vs 12%, P = 0.84). The 30-day morbidity rate was also unchanged (24% vs 25%, P = 0.83), as was length of intensive care unit stay (3 vs 3 days, P = 0.74). Overall length of stay was not significantly different (8 vs 6 days, P = 0.76). Subgroup analysis of patients with elective, ruptured, and symptomatic aneurysm repair demonstrated no differences in 30-day mortality. There was a significantly shorter stay post-centralization for patients with symptomatic aneurysms (6 vs 12 days pre-centralization, P = 0.012). Conclusions: The process of centralization of abdominal aortic aneurysm repair in a vascular network was safe for patients and had no immediate impact on outcomes. Longer-term outcome measures and financial data will be required to further assess the benefit of centralization.